Association between urinary exposures and the risk of chronic obstructive pulmonary disease in smokers: results from NHANES 2007–2016 - Hongli Xu; Weiwei Chen; Jinjun Sun (Frontiers in Public Health)
ObjectiveThis study aims to shed light on the connection of urinary exposures with risk of chronic obstructive pulmonary disease (COPD) among smokers, thereby providing scientific evidence for the prevention and intervention of COPD.MethodsData of the National Health and Nutrition Examination Survey (NHANES) 2007–2016 were utilized, including 3,973 smokers aged 20 or older. We employed the weighted multivariate logistic and weighted quantile sum (WQS) regression models to delve into the link of urinary concentrations of exposures to COPD risk. Additionally, restricted cubic spline regression was utilized to examine the dose–response relationship between biomarker concentrations and COPD risk. The stability of the associations across different participant characteristics was evaluated through subgroup and mediation analyses.ResultsOur study encompassed a total of 3,973 participants, of whom 472 were diagnosed with COPD. Regression analyses revealed the inverse association between urinary concentrations of benzophenone-3 (BP-3) and propyl paraben (PrP) and COPD risk. Higher quartiles of BP-3 and PrP exhibited lower COPD incidence [BP-3: odds ratio (OR) = 0.64, 95% confidence interval (95%CI) (0.47, 0.89), p = 0.007; PrP: OR = 0.56, 95%CI (0.36, 0.86), p = 0.008]. Significant synergistic interactions among urinary exposures were observed [WQS: 0.75, 95%CI (0.65, 0.88), p = 0.026], with BP-3 and PrP contributing 40.31 and 40.01% to the weighted analysis, respectively. Mediation analysis proved that inflammatory markers, such as white blood cell (WBC) count and neutrophil-to-lymphocyte ratio (NLR), significantly mediated the association between BP-3, PrP, and COPD risk (all p-values <0.05).ConclusionBP-3 and PrP in environmental exposure in smokers have an inverse correlation with COPD risk, with WBC and NLR partially mediating this association.